Evaluation of neonatal brain myelination using the T1‐ and T2‐weighted MRI ratio. Issue 3 (26th December 2016) - Soun, Jennifer E.; Liu, Michael Z.; Cauley, Keith A.; Grinband, Jack
Abstract : Purpose: To validate the T1‐ and T2‐weighted (T1w/T2w) MRI ratio technique in evaluating myelin in the neonatal brain. Materials and Methods: T1w and T2w MR images of 10 term neonates with normal‐appearing brain parenchyma were obtained from a single 1.5 Tesla MRI and retrospectively analyzed. T1w/T2w ratio images were created with a postprocessing pipeline and qualitatively compared with standard clinical sequences (T1w, T2w, and apparent diffusion coefficient [ADC]). Quantitative assessment was also performed to assess the ratio technique in detecting areas of known myelination (e.g., posterior limb of the internal capsule) and very low myelination (e.g., optic radiations) using linear regression analysis and the Michelson Contrast equation, a measure of luminance contrast intensity. Results: The ratio image provided qualitative improvements in the ability to visualize regional variation in myelin content of neonates. Linear regression analysis demonstrated a significant inverse relationship between the ratio intensity values and ADC values in the posterior limb of the internal capsule and the optic radiations (R 2  = 0.96 and P  < 0.001). The Michelson Contrast equation showed that contrast differences between these two regions for the ratio images were 1.6 times higher than T1w, 2.6 times higher than T2w, and 1.8 times higher than ADC (all P  < 0.001). Finally, the ratio improved visualization of the corticospinal tract, one of the earliest myelinated pathways. Conclusion: The T1w/T2w ratio accentuates contrast between myelinated and less myelinated structures and may enhance our diagnostic ability to detect myelination patterns in the neonatal brain. Level of Evidence: 2 Technical Efficacy: Stage2 J. MAGN. RESON. IMAGING 2017;46:690–696